Barriers to gender-based violence care: a qualitative study of migrant and refugee women - Bradley, Kathleen (Department of Public Health and Family Medicine, 2025)
South Africa has long served as a destination for migrants from sub-Saharan African nations, with a growing proportion of this population being women in recent years. Female migrants experience an increased risk for gender-based violence (GBV) during the migratory journey and upon resettlement. Accessible and culturally sensitive health, psychosocial, and justice services are necessary to promote holistic recovery for survivors. However, numerous barriers, influenced by widespread xenophobia and increasingly restrictive immigration legislation, have limited this population's access to care. The study aims to explore the barriers encountered by female migrants when accessing care services following experiences of GBV. This qualitative, exploratory study was conducted in Cape Town, South Africa between June and December 2023. Participants were purposively sampled and recruited in partnership with a local migrant organization. Their countries of origin included Burundi, the Democratic Republic of Congo, and Zimbabwe. Data was collected through face-to-face, semi-structured in-depth interviews with 12 female migrants and four key informant (KI) service providers. Interviews explored women's experiences of accessing and utilizing post-violence care services. Inductive thematic analysis guided the study. Data analysis revealed that within a context of xenophobic discrimination and economic instability, female migrants face multiple obstacles in the accessibility and acceptability of post-violence care services. Notable themes in accessibility include a lack of access to information deriving from participants' severe levels of isolation and language barriers. This is compounded by social inaccessibility due to cultural norms against reporting GBV and bureaucratic inaccessibility from prolonged documentation processes. Acceptability of services found multiple reports of xenophobic treatment and victim-blaming behaviour from service providers which impacted women's willingness to seek care. However, many still expressed generally positive sentiments about the progressive nature of social services in South Africa in contrast to their home countries. A lack of information about available postviolence resources, language and cultural barriers, as well as bureaucratic challenges, are limiting the migrant woman's ability to seek help following instances of GBV in Cape Town. Findings demonstrate how non-governmental organizations and individual citizens are currently filling a gap in referrals and service provision raising concerns about sustainability. Advocacy and government intervention are necessary to ensure post-violence care services can adequately meet the needs of migrant women. This mini-dissertation is comprised of two components; Part A is the research protocol for how the study was conducted and Part B in a journal manuscript detailing the process and findings of the study.